ANALISIS RISIKO DAN KERUGIAN KEBAKARAN DAN LEDAKAN PADA TANGKI PENDAM PERTAMAX DI STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) X DENGAN METODE DOW’S FIRE AND EXPLOSION INDEX - Novita Affuwani; Amiruddin, Jafar; Yoga, Nugroho Gama (LPPM, Universitas Negeri Jakarta, 2021)
In the process of its activities, SPBU (General Fuel Filling Station) X has the risk of fire and explosion because there is storage and distribution of flammable liquid fuel, one of which is Pertamax. Therefore, it is necessary to evaluate the risk control of the incident in order to reduce the losses incurred. This study aims to determine the risk of fire and explosion, as well as the value of business interruption (BI) or the value of possible losses suffered in the event of a fire and explosion. The risk assessment method used is the Dow's Fire and Explosion Index. The results of the study indicate that the potential for fire and explosion or the value of the fire explosion index (F&EI) is 110.828. This figure shows that the level of potential fire and explosion hazard in the Pertamax storage tank with a capacity of 21,694 liters at SPBU X is classified as Intermediate. The exposure radius is 28.39 meters and the damage factor to the pertamax buried tank is 63%. The large area of ​​the Exposure is 24 m2 with the exposed area as large as the volume of the bunker building of 96 m3. This means that pertamax containment tanks require special safety and security attention in order to reduce the value of the risk level. The value of the loss suffered by the company in the event of a fire and explosion in the Pertamax tank is Rp. 403.908076.97 Keywords: Dow's Fire and Explosion Index, Risk Level, Gas Station, Buried Tank, Pertamax.